Third Five Year Plan Progress Report 1962-63 Madhya Pradesh - Planning Commission (Planning Commission, 1962)
The basic objectives of the National Five Year Plans as also of the Stale Plans is to provide a sound foundation for sustained economic growth for employment opportunities and improving living standards of the masses of people. The first two five year plans have helped to strengthen the economic structure of the State and enabled the planners to chalk out a much bolder Third Plan with a larger outlay touching almost every aspect of the community life. The total outlay for the Third Plan of Madhya Pradesh is Rs. 300,00.00 lakhs.
Directorate of Economics and Statistics, Madhya Pradesh